Addressing Social and Environmental Issues in research and development programmes in agriculture - Agrawal, K P (Indian Farming, 2015)
The gain of green revolution technologies wa available to about 30% of irrigated area in the country while the remaining 70% of the rainfed area languished without larger support of improved technologies. The high production in limited areas resulted in stagnation or fall in productivity and lesser production of nutritious crops by the dint of crop substitution. The green revolution technologies did lot of damage to ecology and social profile and were not found sustainable in the long run.